2010
DOI: 10.1063/1.3428780
|View full text |Cite
|
Sign up to set email alerts
|

Biexciton emission from sol-gel ZnMgO nanopowders

Abstract: Surface related and intrinsic exciton recombination dynamics in ZnO nanoparticles synthesized by a sol-gel method Appl. Phys. Lett. 102, 013109 (2013); 10.1063/1.4774002 High-excitation effect on photoluminescence of sol-gel ZnO nanopowder Appl. Phys. Lett. 96, 081903 (2010); 10.1063/1.3327338 Sol-gel synthesis and nonlinear optical transmission in Zn ( 1 − x ) Mg ( x ) O ( x 0.2 ) thin films Appl. Phys. Lett. 89, 063102 (2006); 10.1063/1.2335375 Confinement-enhanced biexciton binding energy in ZnO/ZnMgO multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Zn 1– x Mg x O ( x = 0, 3.0, 7.0, and 10.0%) powders were synthesized by the citric-acid-assisted sol–gel method as described elsewhere. , The wurtzite phase of the Zn 1– x Mg x O powders at ambient pressure was identified by XRD. The morphology of the powders was studied using scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn 1– x Mg x O ( x = 0, 3.0, 7.0, and 10.0%) powders were synthesized by the citric-acid-assisted sol–gel method as described elsewhere. , The wurtzite phase of the Zn 1– x Mg x O powders at ambient pressure was identified by XRD. The morphology of the powders was studied using scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…The deviations of Mg contents at various positions in the samples were 3.0 ± 0.3%, 7.0 ± 0.5%, and 10.0 ± 0.5%, as determined by EDX measurements. The photoluminescence , and Raman spectra recorded at different positions throughout the samples were all identical.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In our previous letter, we reported the biexcitonic emissions of sol-gel Zn 1Àx Mg x O powders. 3 It was found that the emission of a longitudinal-optical (LO) phonon sideband is obvious in the sol-gel Zn 1Àx Mg x O powders at high temperature (T). As excitation density increases, the exciton-phonon interaction competed with the inelastic exciton-exciton scattering process, which is an important transition for stimulated emission in ZnO-based nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Incorporating Mg into ZnO thin film has already been proved to be a feasible technique to realize band gap tuning since the band gap of wurtzite ZnO is 3.37 eV and that of MgO is 7.4 eV. 5 Additionally, ZnMgO can be used as barrier layers for carrier confinement as well as in waveguides and distributed Bragg reflectors.…”
mentioning
confidence: 99%